A CRISPR/Cas9-mediated screen identifies determinants of early plasma cell differentiation - Xiong, Ermeng; Popp, Oliver; Salomon, Claudia; Mertins, Philipp; Kocks, Christine; Rajewsky, Klaus; Chu, Van Trung (Frontiers in Immunology, 2023)
The differentiation of B cells into antibody-secreting plasma cells depends on cell division-coupled, epigenetic and other cellular processes that are incompletely understood. We have developed a CRISPR/Cas9-based screen that models an early stage of T cell-dependent plasma cell differentiation and measures B cell survival or proliferation versus the formation of CD138+ plasmablasts. Here, we refined and extended this screen to more than 500 candidate genes that are highly expressed in plasma cells. Among known genes whose deletion preferentially or mostly affected plasmablast formation were the transcription factors Prdm1 (BLIMP1), Irf4 and Pou2af1 (OBF-1), and the Ern1 gene encoding IRE1a, while deletion of XBP1, the transcriptional master regulator that specifies the expansion of the secretory program in plasma cells, had no effect. Defective plasmablast formation caused by Ern1 deletion could not be rescued by the active, spliced form of XBP1 whose processing is dependent on and downstream of IRE1a, suggesting that in early plasma cell differentiation IRE1a acts independently of XBP1. Moreover, we newly identified several genes involved in NF-kB signaling (Nfkbia), vesicle trafficking (Arf4, Preb) and epigenetic regulators that form part of the NuRD complex (Hdac1, Mta2, Mbd2) to be required for plasmablast formation. Deletion of ARF4, a small GTPase required for COPI vesicle formation, impaired plasmablast formation and blocked antibody secretion. After Hdac1 deletion plasmablast differentiation was consistently reduced by about 50%, while deletion of the closely related Hdac2 gene had no effect. Hdac1 knock-out led to strongly perturbed protein expression of antagonistic transcription factors that govern plasma cell versus B cell identity (by decreasing IRF4 and BLIMP1 and increasing BACH2 and PAX5). Taken together, our results highlight specific and non-redundant roles for Ern1, Arf4 and Hdac1 in the early steps of plasma cell differentiation.